The PhD parenthood trap : caught between work and family in academia - Crawford, Kerry F.; Windsor, Leah C. (Georgetown University Press, 2021)
"The PhD Parenthood Trap gives voice to the struggles lived by parents in academia and identifies avenues to better approaches. Kerry F. Crawford and Leah C. Windsor present insights from original survey data and vignettes that they have collected from scholars across disciplines. Topics include pregnancy, miscarriage and infant loss, family leave, breastfeeding, daily parenting challenges, and more. The authors have found that universities and their departments are displaying a lack of understanding, uniform policies, support, and flexibility for family formation and parenting, which is hurting the career development of parent-scholars, especially women. The authors conclude each chapter with recommendations for best practices and needed changes in order to make academia an exemplar of progressive family leave policies. The PhD Parenthood Trap is a rallying cry for parents in academia and it also seeks to educate university and department administrators in order to encourage meaningful change"--